The Urgency of Land Deed Officials (PPAT) Role in the Transfer of State-Owned Land Under A Legal Perspective - Kurniawan, Edi; Hariansah, Syafri (Law Development Journal, 2025)
The transfer of State-Owned Assets (BMN) in the form of land is a legal process that must comply with administrative and land law regulations. The issue of an authentic deed by a Land Deed Official (PPAT) is an essential instrument in the transfer of land rights. This study seeks to analyze the legal ramifications of conducting the process without a PPAT deed and to assess the importance of PPAT in validating property rights transfers, including BMN. The applied research methodology is normative juridical, utilizing a statutory and case study approach. The results demonstrate that the conveyance of land rights does not comply with the legal stipulations set forth by national land laws in the absence of a deed executed by a PPAT, which may lead to disputes and financial losses for the state. This report promotes the strengthening of regulations mandating PPAT involvement in all BMN land transfers to ensure legal certainty and protect state interest.